The Influence of Counseling Guidance, Parenting Patterns, and School Environment on Students' Learning Independence at MA Darut Taqwa Semarang - Irfangi, A Mukhsin; We, Soetomo; Triani A, Aurilia (Journal of Social Research, 2023)
This study analyzes and explains the effect of counseling guidance, parenting patterns, and school environment on the learning independence of students who experience unfavorable conditions because it is seen that in schools there are still violations of school rules. This is because the counseling guidance is not running optimally. The data obtained were processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis uses multiple regression analysis to determine the effect of the independent variable on the dependent variable, but before the test is carried out, the validity and reliability tests are carried out first. The results of the regression analysis show that counseling guidance, parenting patterns of parents, and the school environment significantly affect students' learning independence with a positive product-moment correlation, this indicates an increase in counseling guidance, parenting patterns of parents, and the school environment will be followed by an increase in students' learning independence, vice versa. The results of the multiple regression analysis test showed a significant F value, with a correlation of 0.439. This shows that counseling guidance, parenting patterns of parents, and the school environment significantly affect the learning independence of students with a close relationship of 43.9%. Counseling guidance, parenting patterns of parents, and the school environment affect the learning independence of students in real terms, both individually and collectively. This shows that to increase the learning independence of students, it is necessary to increase counseling guidance, improve parenting patterns, and improve the school environment.